A study of competitive behaviour of Malaysian commercial banks using structural and non-structural model / Sutina Junos, Mahadzir Ismail and Irlisuhayu Mohd Ramli - Junos, Sutina; Ismail, Mahadzir; Mohd Ramli, Irlisuhayu (Research Management Institute, 2012)
Being competitive is seen as a prerequisite for future sustainability. This study aims to investigate the degree of competitiveness of the Malaysian banks for the period between 1995 and 2010 using both structural and non-structural models. For the structural model, we use three market concentration measures namely CR3, CR5 and Herfindahl index. For the later approach, we use the Panzar-Rosse model whereby we perform both equilibrium and competitive test. Three input prices are used, the price of labour, the price of capital and the price of deposit. We also use three banks specific variables. Based on the structural model, the Malaysian banking industry shows the presence of mild market power given a moderate degree of concentration and the presence of mild competition. The PR model, on the other hand, shows stronger presence of competition as the H-statistics is close to 1. Part of the results confirms earlier findings that the Malaysian banking industry is best described as monopolistic competition.